The certification role of the EU-wide stress testing exercises in the stock market: What can we learn from the stress tests (2014-2021)? - Agha Durrani; Steven Ongena; Aurea Ponte Marques (European Central Bank (ECB), 2022)
What is the impact of stress tests on bank stock prices? To answer this question we study the impact of the publication of the EU-wide stress tests in 2014, 2016, 2018, and 2021 on the first (λ) and second (δ) moment of equity returns. First, we study the effect of the disclosure of stress tests on (cumulative) excess/abnormal returns through a one-factor market model. Second, we study whether both returns and volatility of bank stock prices changes upon the disclosure of stress tests through a structural GARCH model, developed by Engle and Siriwardane (2018). Our results suggest that the publication of stress tests provides new information to markets. Banks performing poorly in stress tests experience, on average, a reduction in returns and an increase in volatility, while the reverse holds true for banks performing well. Banks performing moderately have rather a small effect on both mean and variance process. Our findings are corroborated by the observed rank correlation between bank abnormal returns or equity volatility and stress test performance, which experiences a steady increase after each publication event. These results suggest that the publication of stress tests improves price discrimination between 'good' and 'bad' banks, which can be interpreted as a certification role of the stress tests in the stock market.
Keywords: G11; G14; G21; G28; 330; Stress tests; Financial stability; Stock markets; Excess return; Volatility